2021
DOI: 10.3390/su13041710
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media and Its Impact on Shopping Behavior of Slovak and Italian Consumers during COVID-19 Pandemic

Abstract: The coronavirus crisis hit the world and affected all aspects of our lives, including consumers’ habits, preferences, and shopping behaviors. The survey, which involved 937 respondents from two countries, examined how the pandemic affected shopping behavior and consumer preferences in Italy and Slovakia. This paper aims to explore the impact of social media on consumer behavior, more specifically, it examines the influence of social media on the preference of specific e-shops during the first wave of the COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 29 publications
2
47
0
1
Order By: Relevance
“…The coronavirus epidemic had a significant effect on online sales, especially over the weekend (COVID-19). Thus, the adoption of the contemporary technology tools using internet has shown a significant importance in changing consumer behavior in China ( Ali Taha et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus epidemic had a significant effect on online sales, especially over the weekend (COVID-19). Thus, the adoption of the contemporary technology tools using internet has shown a significant importance in changing consumer behavior in China ( Ali Taha et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some researcher for example, Abbas et al (2019) found the negative impact of using social media of student learning behavior. Taha et al (2021) showed a significant difference in use of SM during the first wave of the COVID-19 pandemic which may impact on consumer behavior. However, the study showed that social media has significant influence on raising EA and generating PA to mass tourists' which significantly impact to tourists' ERB.…”
Section: Conclusion 1 Discussionmentioning
confidence: 99%
“…Tourists may respond to environmental stimuli by developing subjective awareness about their entire tourism experience. The consumer then chooses whether to continue using the service or not (Taha et al, 2021). Tourists are more prone to adopt social media-related habits than visitors who have less integration and knowledge of the environment (Javed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social media is having a substantial impact on consumers' purchase behaviour. Millennials are currently the most populous generation globally (Taha, Pencarelli, Škerháková, Fedorko, & Košíková , 2021) and represent the highest-spending generation in 2020 -with a projected $1.4 trillion (Kasasa, 2021). Generation Y is the newcomer both in the workplace and visitors category.…”
Section: Introductionmentioning
confidence: 99%